Determining the size of energy storage system to maximize the economic profit for photovoltaic and wind turbine generators in South Korea - Kong, Junhyuk; Kim, Sung Tae; Kang, Byung O.; Jung, Jaesung (Renewable and Sustainable Energy Reviews, 2019)
This study identifies the optimal size of an Energy Storage System (ESS) for Photovoltaic (PV) and Wind Turbine (WT) generators under current Korean government policies. The government has pledged to promote the use of ESS with PV and WT generation to reduce the variability and uncertainty of renewable energy generation. The proposed algorithm determines the optimal ESS size required for PV and WT suppliers to maximize economic profit by using their historical generation profiles and compensation price. Net Present Value (NPV) is used as an economic parameter to determine the optimal size of ESS and consequently, the optimization indicates the maximization of NPV in this study. Furthermore, this paper proposes a methodology to estimate the size of ESS when there is insufficient information for future PV and WT suppliers. To verify the proposed algorithms, actual PV and WT generation profiles as well as the compensation price in South Korea are used. The simulation results indicate that the optimal capacity ratio between Renewable Energy Source (RES), ESS battery, and ESS PCS is determined as 1:3.3:0.7 and 1:3:1 for PV and WT respectively. Furthermore, the ESS size estimated by the proposed methodology shows a marginal difference from the optimal size, with an error of less than 3% for PV and 0% for WT.
Keywords: Economics analysis; Energy storage system; Energy storage system sizing; Estimation models; Photovoltaic; Photovoltaics; Storage systems; System sizings; Wind turbine; Economic analysis; Energy storage system (ESS); ESS sizing; Estimation model; Photovoltaic (PV); Wind Turbine (WT)